Hubungan Indonesia-Australia - Sarkawi B. Husain (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2023)
Indonesia and Australia are two countries that have long historical and diplomatic relations. Unfortunately, studies on these various relationships, both in the journals and books, are very limited. Therefore, this book is very important to help us understand relationship between the two countries. This book give an important contribution in adding to the collection of important works about Australia written in Indonesian. This book explains how Australian foreign policy in general grew out of Australia's concerns and beliefs (or perceptions), and how it came to shape and develop further. This is supported by the author's careful and systematic explanation of the social context in which the basic assumptions underlying Australia's foreign policy are formed. Today, Indonesia-Australia relations are very close. Several programs were initiated such as Economic Management, Infrastructure, Water, Sanitation, and Hygiene. By collaborating with a number of institutions of the Government of the Republic of Indonesia, the Australian government helps to promote strong economic growth, sustainable economic growth that can be enjoyed by all people.